Hematometrocolpos following Low Transverse Cesarean Delivery Complicated by Uterine Dehiscence - Lauryn C. Gabby; Katherine E. McDaniel; Brian J. Gordon; Laila A. Al-Marayati (Case Reports in Obstetrics and Gynecology)
Background. Hematometrocolpos is a rare complication following procedures performed on the female genital tract. While usually seen in adolescents with congenital anomalies including imperforate hymen and vaginal stenosis, it has also been described following obstetric vaginal lacerations. The incidence following cesarean delivery is unknown. Case. This is a 43-year-old multigravida who underwent a low transverse cesarean delivery complicated by uterine dehiscence, as well as cervical and vaginal lacerations. The repair resulted in lower genital tract obstruction. She presented seven months afterwards with severe abdominopelvic pain and secondary amenorrhea, which resolved after vaginal dilation and excision of the vaginal scar. Conclusion. Systematic inspection of the upper vagina should be undertaken following complicated cesarean delivery with vaginal extension. Hematometrocolpos after cesarean delivery should be managed similar to a transverse vaginal septum.